2013
DOI: 10.1371/journal.pone.0070126
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based CD4 Counts in a Rural Area in South Africa with High HIV Prevalence and High Antiretroviral Treatment Coverage

Abstract: BackgroundLittle is known about the variability of CD4 counts in the general population of sub-Saharan Africa countries affected by the HIV epidemic. We investigated factors associated with CD4 counts in a rural area in South Africa with high HIV prevalence and high antiretroviral treatment (ART) coverage.MethodsCD4 counts, health status, body mass index (BMI), demographic characteristics and HIV status were assessed in 4990 adult resident participants of a demographic surveillance in rural KwaZulu-Natal in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
29
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 47 publications
(54 reference statements)
11
29
1
1
Order By: Relevance
“…The study population was predominantly female, consistent with previously reported data [9,13,14], and probably reflecting higher population‐level CD4 cell counts among women [15] and the different entry points into HIV care. Previous work did not find any association between sex and disease progression pre‐ART initiation [4]; however, mortality after ART initiation is consistently higher in men [16].…”
Section: Discussionsupporting
confidence: 89%
“…The study population was predominantly female, consistent with previously reported data [9,13,14], and probably reflecting higher population‐level CD4 cell counts among women [15] and the different entry points into HIV care. Previous work did not find any association between sex and disease progression pre‐ART initiation [4]; however, mortality after ART initiation is consistently higher in men [16].…”
Section: Discussionsupporting
confidence: 89%
“…The cohorts demographics are characteristic of HIV epidemiology in South Africa, where patients frequently present with advanced disease, women invariably being younger . Median CD4 counts were low, although somewhat higher in women, a feature previously observed . Since 2007, given significant policy change and a public program, more than half of the cohort were on HAART; and this likely contributed to the prevalent finding of DILI …”
Section: Discussionmentioning
confidence: 69%
“…38–40 Among these baseline states, simulated mean CD4 varied from 380 (SD 190) cells/µL for those on ART to 560 (SD 230) cells/µL for those with acute infection (Table 2). 37,41,42 We assumed that individuals who are eligible for but not on ART at baseline would initiate therapy with a monthly probability of 15%, reflecting enhanced efforts to provide access to ART in the context of a trial. 13 …”
Section: Methodsmentioning
confidence: 99%
“… b CD4 distributions are truncated normal distributions calibrated to match data from references 41 (acute infection), 37 (undiagnosed, chronic), and 42 (off ART, first-line, and second-line). …”
Section: Figurementioning
confidence: 99%